The Impact of Cultural Distance and Political Risk on SMEs’ Internationalization Strategies: The Case of SMEs in the UAE and Lebanon - Slaiby, Walid; Matta, Fadia (International Review of Management and Marketing, 2025)
This paper aims to study the effects of cultural distance and political risk on the Middle East international SMEs’ choice of entry mode to the foreign target markets relative to their resource commitment. The SMEs were studied from two countries the United Arab Emirates (UAE) and Lebanon. The market entry could be either through non-equity entry modes (exports and contractual agreements) or equity entry modes (shared and full ownership/ control of foreign direct investments). The respondents of this study were owners and managers of UAE and Lebanese international SMEs. We obtained primary data through a survey using a semi-structured questionnaire. We studied the attitudes of SME owners and managers by using a quantitative method, statistically analyzing the responses using a one-sample T-test and the Spearman correlation coefficient. The findings show that when cultural distance is high between UAE/Lebanon and the host country, the SMEs tend to prefer less commitment in terms of financial resources. Therefore, the contingency approach suggests that high cultural distance leads investors to favor entry modes with greater flexibility, enabling easy dissolution in the event of failure. When looking at how political risk affected the choice of entry mode for UAE and Lebanon’s small and medium-sized businesses into international markets, it seemed that these businesses would rather commit fewer resources and limit their financial loss in case they fail. This supports the Transaction Cost Theory, which says that foreign investors are unwilling to commit many resources in a high political risk environment. In addition, the research findings confirm the contingency approach since both UAE and Lebanon SMEs tend to choose non-equity entry modes to have a flexible position to be able to dissolve their commitment when they face unfavorable changes in environmental conditions. Furthermore, the results show that UAE and Lebanon SMEs don’t seem to agree with choosing high-commitment full ownership/control FDI as an entry mode in a high-political-risk context. The originality of this research is its emphasis on UAE and Lebanon SMEs’ internationalization strategies and how these companies with limited resources could build on key success factors for developing their businesses in new markets.